Case Report: Crossing a rugged road in a primary immune regulatory disorder - Sgrulletti, Mayla; Cifaldi, Cristina; Di Cesare, Silvia; Kroegler, Barbara; Del Duca, Elisabetta; Ferradini, Valentina; Graziani, Simona; Bengala, Mario; Di Matteo, Gigliola; Moschese, Viviana (Frontiers in Pediatrics, 2023)
Over the last decades, Inborn Errors of Immunity (IEI) characterized by an immune dysregulatory picture, isolated or combined with infections, have been increasingly identified and referred as Primary Immune Regulatory Disorders (PIRD). PIRD diagnosis may be difficult due to heterogeneity of time onset, sequence of clinical manifestations and laboratory abnormalities. Moreover, the dissection of a PIRD vs a secondary immunodeficiency (SID) might be a real challenge since the same indications for immunosuppressant treatments might represent per se a PIRD clinical expression. Here we report a female patient with a history of recurrent respiratory and urinary tract infections since early infancy and a diagnosis of Rheumatoid Arthritis in adulthood. After poor response to several biologicals she was treated with Rituximab and sent to immunology referral for a severe hypogammaglobulinemia. Clinical and immunological features matched a diagnosis of common variable immunodeficiency and when IgG replacement therapy and antibiotic prophylaxis were added a good infectious control was obtained. Next generation sequencing analysis has revealed a novel heterozygous VUS in the IKBKB gene (c.1465A>G; p.Ser489Gly). Functional analysis has shown a reduced capacity of B lymphocytes and CD4 positive T cells in inducing IκBα degradation, with negative impact on NF-kB pathway. Due to recurrent infections attributed to a common condition in childhood and to an exclusive autoimmunity-centered approach in adulthood, both diagnosis and suitable treatment strategies have suffered a significant delay. To reduce the diagnostic delay, pediatricians, general practitioners and specialists should be aware of IEI and the challenges to differentiate them from SID. Furthermore, genetic characterization and functional analysis may contribute to a personalized approach, in a perspective of targeted or semi-targeted therapy.